The link between intellectual capital and business performance: A mediation chain approach - Campos, S.; Dias, J. G.; Teixeira, M. S.; Correia, R. J. (Journal of Intellectual Capital, 2022)
Purpose: This study focuses on intellectual capital (IC) as a driver of better business performance. Recent studies suggest that a set of variables may mediate this relationship. This research discusses the mediating role of dynamic capabilities, network competence, technological capabilities, absorptive capabilities and innovation performance between intellectual capital and business performance. Design/methodology/approach: The conceptual model is tested using a sample of 533 Portuguese firms by means of a structural equation model. Findings: It confirms that intellectual capital impacts business performance. Moreover, this only happens indirectly through the mediating chain defined by the variables dynamic capabilities, network competence, technological capabilities, absorptive capabilities and innovation performance. Originality/value: This study analyzes new mediator variables between the dimensions of the intellectual capital and Portuguese business performance.